Conditional cash transfers in Brazil, Chile and Mexico: Impacts upon inequality - Soares, Sergei; Guerreiro Osório, Rafael; Veras Soares, Fábio; Medeiros, Marcelo; Zepeda, Eduardo (Estudios Económicos de El Colegio de México, 2009)
We decompose changes in the Gini coefficient to investigate whether the Conditional Cash Tranfers (CCT) have had an inequality reducing effect in three Latin American countries: Brasil, Mexico and Chile. We conclude that CCT programs helped reducing inequality between the mid-1990s and the mid-2000s. The share of total income represented by the CCTs is very small, less than 1%. But as their targeting is outstanding, the equalising impact of CCTs was responsible for about 21% of the fall in Brazilian and Mexican inequality figures In Chile the effect was responsible for around 15% of the reduction.